2005
DOI: 10.1007/s11136-005-7380-9
|View full text |Cite
|
Sign up to set email alerts
|

Development of the WHOQOL-Old Module

Abstract: This paper describes the development of an add-on module for the WHOQOL measures of quality of life (QoL) for use with older adults. The add-on module, known as the WHOQOL-OLD, was derived following standard WHOQOL methodology. In the pilot phase of the study, 22 centres from around the world carried out focus groups with older adults, with carers, and with professionals working with older adults in order to identify gaps in the coverage of the WHOQOL-100 that were relevant for QoL in older adults. Items gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
464
4
51

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 492 publications
(544 citation statements)
references
References 11 publications
25
464
4
51
Order By: Relevance
“…The coefficients are close to the ones described for the whole international sample (Power et al, 18 2005) and higher than the ones found in the WHOQOL-100 and WHOQOL-BREF in their validation processes (Fleck et al,12 1999; Fleck et al, 13 2000), corroborating the appropriateness of the module's consistency.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The coefficients are close to the ones described for the whole international sample (Power et al, 18 2005) and higher than the ones found in the WHOQOL-100 and WHOQOL-BREF in their validation processes (Fleck et al,12 1999; Fleck et al, 13 2000), corroborating the appropriateness of the module's consistency.…”
Section: Discussionsupporting
confidence: 74%
“…The aim of the project was to develop and test a generic QoL measurement tool capable of being used in cross-cultural investigations. Although the international development of the WHOQOL-OLD project is described in more details elsewhere (Power et al,18 2005), an overview of the Brazilian Center's participation is provided below.…”
Section: Methodsmentioning
confidence: 99%
“…The sample was comprised using an internationally standardized method, requiring a minimum of 300 participants, stratified by age, gender, and self-rated health 1,21 . This was a convenience sample 22 , and elders with terminal illnesses and dementia were excluded.…”
Section: Methods Participantsmentioning
confidence: 99%
“…-WHOQOL-OLD (Power, Quinn, & Schmidt, 2005;Vilar & Simões, 2009) to evaluate the QoL in older adults (Vilar, Sousa, & Simões, 2015). In original version, it consists of six facets: Sensory Functioning (evaluates the sensory functioning and impact of the loss of sensory abilities participation in activities and interaction), Autonomy (ability to live independently and make decisions), Past, Present and Future Activities (assesses satisfaction with achieved goals in life and projects to accomplish), Social Participation (assesses participation in everyday activities, particularly in the community), Death and Dying (rating concerns and fears about death and dying), and Intimacy (assesses the ability to have personal and intimate relationships), with a Likert scale of five points (1-5).…”
Section: Assessment Toolsmentioning
confidence: 99%